2022
DOI: 10.1111/jfd.13625
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous epitheliotropic lymphosarcoma in a captive white catfish (Ameiurus catus Linnaeus)

Abstract: A wild caught white catfish (Ameiurus catus Linnaeus) developed multiple cutaneous masses. Cytology revealed neoplastic lymphocytes and microscopy confirmed dermal infiltration with epitheliotropism in the epidermis, oral mucosa, and cornea, without internal organ involvement. Transmission electron microscopy did not identify viral particles. Histopathology supported cutaneous epitheliotropic lymphosarcoma, a condition most commonly reported in mammals. This is the first reported case of cutaneous epitheliotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Retroviruses are well established as a cause of lymphoma in many domesticated mammal species [ 18 ] and are suspected of causing cutaneous lymphomas in pike and muskellunge [ 52 , 53 ]. Although viral etiology is suspected in a number of fish hematopoietic tumours (e.g., lymphoma and lymphosarcoma) [ 30 ], there have been some reports of chemically-induced lymphosarcoma. Chen et al [ 54 ] revealed that a chemical carcinogen such as N-methyl-N’-nitro-N-nitrosoguanidine plays a key role in the progression of lymphosarcoma in channel catfish ( Ictalurus punctatus ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retroviruses are well established as a cause of lymphoma in many domesticated mammal species [ 18 ] and are suspected of causing cutaneous lymphomas in pike and muskellunge [ 52 , 53 ]. Although viral etiology is suspected in a number of fish hematopoietic tumours (e.g., lymphoma and lymphosarcoma) [ 30 ], there have been some reports of chemically-induced lymphosarcoma. Chen et al [ 54 ] revealed that a chemical carcinogen such as N-methyl-N’-nitro-N-nitrosoguanidine plays a key role in the progression of lymphosarcoma in channel catfish ( Ictalurus punctatus ).…”
Section: Discussionmentioning
confidence: 99%
“…According to veterinary literature, lymphomas are common in dogs, cats, and pigs, but comparatively rare in horses and other domestic species [ 16 19 ]. Lymphoma, defined as a malignant tumour of lymphoid tissue [ 18 ], has been found in a number of fish species including northern pike ( Esox lucius ) [ 20 , 21 ], Japanese medaka ( Oryzias latipes ) [ 22 , 23 ], coho salmon ( Oncorhynchus kisutch ) [ 24 ], black bullhead ( Ameiurus melas ) [ 25 ], rainbow trout ( Oncorhynchus mykiss ) [ 26 ], flower horn (hybrid cichlid) [ 27 ], gold crossback arowana ( Scleropages formosus ) [ 28 ], Atlantic stingray ( Hypanus sabinus ) [ 29 ] and captive white catfish ( Ameiurus catus Linnaeus) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale pathology reviews monitoring disease occurrence in captivity are sparse; those undertaken indicate that neoplasia is rare when compared to other taxa, with a reported prevalence between 0.4% and 0.5% (Garner, 2013;Stidworthy et al, 2017). Lymphoid neoplasia has to date been reported in a range of teleost fish (Bowser et al, 2002;Harada et al, 1990;Heniff et al, 2022) but only in four elasmobranchs: a sandbar, Carcharhinus plumbeus (Nardo), bonnethead, Sphyrna tiburo (Linnaeus) and white-spotted bamboo shark, Chiloscyllium plagiosum (Anonymous [Bennett]) (Dawe & Berard, 1971;Manire et al, 2013;Rosenberg et al, 2015), and an Atlantic stingray, Hypanus sabinus (Lesueur) (Stilwell et al, 2019). Lymphohaematopoietic neoplasms in fish are primarily derived from lymphoid cells.…”
Section: Introductionmentioning
confidence: 99%